2010
DOI: 10.1302/0301-620x.92b9.24282
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of interventions in the management of patients with primary frozen shoulder

Abstract: There are many types of treatment used to manage the frozen shoulder, but there is no consensus on how best to manage patients with this painful and debilitating condition. We conducted a review of the evidence of the effectiveness of interventions used to manage primary frozen shoulder using the Cochrane Database of Systematic Reviews, the Database of Abstracts of Reviews of Effects, the Physiotherapy Evidence Database, MEDLINE and EMBASE without language or date restrictions up to April 2009. Two authors ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 34 publications
(60 reference statements)
1
38
0
Order By: Relevance
“…These results are similar to those obtained in studies conducted by other researchers. In a study conducted by Waszczykoski et al on 30 patients suffering from frozen shoulder, after a 2-year follow-up, it was seen that arthroscopic release improved significantly shoulder range of motion and function in primary and secondary frozen shoulders (14)(15)(16)(17). Our study obtained similar results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are similar to those obtained in studies conducted by other researchers. In a study conducted by Waszczykoski et al on 30 patients suffering from frozen shoulder, after a 2-year follow-up, it was seen that arthroscopic release improved significantly shoulder range of motion and function in primary and secondary frozen shoulders (14)(15)(16)(17). Our study obtained similar results.…”
Section: Discussionsupporting
confidence: 86%
“…In Ozbaydar et al study on 16 patients with frozen shoulder who had arthroscopic selective capsular release, it was seen that patients not responding to conservative treatment were treated effectively by this method (5). In Rookmomeea et al study, after review of different methods of frozen shoulder treatment in various articles, no definitive and effective method was recognized (17). In another study by Musil et al on 27 patients with frozen shoulder, they found that arthroscopic release is the preferred treatment in patients who do not respond to conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The need for standardisation in diagnosis has recently been emphasised and a system of terminology and classification based on consensus would be advantageous. 1 In this review, we use the term frozen shoulder, as it is the most commonly used and avoids the ambiguities associated with terms that attempt to describe the underlying pathology.…”
Section: Definitions and Terminologymentioning
confidence: 99%
“…A multidisciplinary approach is preferable, and most patients can be managed non-operatively in a primary care setting with the expectation of a good outcome. There are many alternative forms of treatment for this condition, but evidence of their efficacy is not well-established from clinical trials, 1 and it is unclear if several interventions used in combination are better.…”
Section: Treatmentmentioning
confidence: 99%
“…Treatment methods include oral analgesics, oral glucocorticoids, intraarticular glucocorticoids, physiotherapy, manipulation and arthroscopic release [3][4][5][6] . These modalities can be used separately or in combinations but effectiveness of each of this method is different in various clinical trials 7 . Oral glucocorticoids and home exercise program is very effective in first stage of frozen shoulder 8 but many studies have mentioned physiotherapy alone with analgesics as good tool to relive pain and gain long term range of motion.…”
Section: Introductionmentioning
confidence: 99%